Targeting transgenic proteins to alpha granules for platelet-directed gene therapy - Vanessa M.A. Woods; Lisette J. Latorre-Rey; Franziska Schenk; Marcel G.E. Rommel; Thomas Moritz; Ute Modlich (Elsevier, 2022)
Platelets are anucleate blood cells that are shed from megakaryocytes (MKs) into the bloodstream to maintain hemostasis and promote wound healing after vascular injury. To carry out their functions, platelets become activated and release bioactive substances from their secretory granules. As alpha granules (αGs) in resting platelets store proteins and release them only after activation, the packaging of proteins into αGs is an attractive strategy to deliver therapeutic proteins. Here, we propose an adjustable model for targeting transgenic proteins to platelet αGs using third-generation self-inactivating lentiviral vectors. The vectors express from the murine platelet factor 4 promoter (mPf4P), restricting transgene expression to the MK lineage. For the delivery and retention of expressed proteins in αGs, proteins are fused to short peptide sorting signals derived from the human cytokine RANTES or from the transmembrane protein P-selectin. We demonstrate effective targeting of GFP to αGs of murine and human in vitro-differentiated MKs and murine platelets in vivo. Furthermore, interferon-α (IFNα), as a potentially therapeutic cytokine, was successfully delivered to and stored in murine platelets in vivo, was released after activation, and inhibited virus replication in vitro. Our vectors create possibilities for numerous applications in cell therapy utilizing platelets as carriers of therapeutic proteins.